Consumers’ Satisfaction Towards Recreational Facilities and Services in Ayer Keroh Forest Recreational Area, Melaka - A. Rahman, Azman (2007)
With the present emphasis on ecotourism, many nature and recreational areas are facing increases in demand. As a result more pressures are being inflicted on the forest recreational areas and other natural areas to provide recreational facilities to users. Facilities in the park are essential to satisfy the needs of visitors; an inadequate provision of facilities and services rendered could lead to congestion and overuse of the facilities; and a lack in services may lessen visitors’ satisfaction. The study was carried out in Ayer Keroh Forest Recreation Area using a sample of 385 visitors. The main aim of this study was to determine and evaluate the visitors’ satisfaction towards the facilities and services provided. Leisure is the most popular past time activity, particularly, among the Malay visitors compared to other ethnic groups. They come in groups, either with family members or friends for picnic which was their main purpose of visits. The visitors find that existing public amenities very satisfactory and suitable for family activities. The mean value of the WTP is RM 21.45 per year. The total index of the perception on facilities and services is at 2.88 which mean is positive perception. There are four predictors of recreation valuation namely amount spend for the facilities and services, perception on sign facilities, participate in recreation activities and income and the result shows that respondents income have significantly influenced the WTP.